(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
The present paper is the second of a series dedicated to Pliocene molluscs of Liguria. lt deals with 13 gastropods species belonging to the superfamilies Rissoacea, Rissoinacea, Cerithiopsacea and Triphoracea. The generic assignment of each taxon is reviewed on the basis of the protoconch characters, and the description is provided for less known species. The genera Cerithiopsidella and Retilaskeya are quoted for the first time in Mediterranean area as well as Rissoina (Rissoina) varicosa Boettger and Metaxia abrupta (Watson). The new species Alvania (Alvania) obliquistoma is proposed.